Three dimensional path planning algorithm for small UAVs incorporating existing dynamic soaring heuristics - Ariff, Omar Kassim (2013)
An area under consideration of improving the mission effectiveness of small-scale, autonomous Uninhabited Aerial Vehicles (UAVs) has been the increase of speed. One method is to incorporate dynamic slope soaring maneuvers as part of the flight path during waypoint navigation. Research into autonomous dynamic soaring capability in small-scale UAVs began with selecting a suitable maneuver heuristic. The output from the heuristic model has then been used to formulate a non-iterative trajectory forming algorithm. By utilizing Dubin’s curves, a viable trajectory can be generated between the exit point of the dynamic soaring maneuver and the next waypoint. The result is a complete, easily implemented three-dimensional autonomous dynamic soaring capability.